Structural determinants for recognition and translocation by the anandamide transporter - Piomelli, D. (The National Academy of Sciences, 1999)
The biological actions of anandamide (arachidonylethanolamide), an endogenous cannabinoid lipid, are terminated by a two-step inactivation process consisting of carrier-mediated uptake and intracellular hydrolysis. Anandamide uptake in neurons and astrocytes is mediated by a high-affinity, Na(+)-independent transporter that is selectively inhibited by N-(4-hydroxyphenyl)-arachidonamide (AM404). In the present study, we examined the structural determinants governing recognition and translocation of substrates by the anandamide transporter constitutively expressed in a human astrocytoma cell line. Competition experiments with a select group of analogs suggest that substrate recognition by the transporter is favored by a polar nonionizable head group of defined stereochemical configuration containing a hydroxyl moiety at its distal end. The secondary carboxamide group interacts favorably with the transporter, but may be replaced with either a tertiary amide or an ester, suggesting that it may serve as hydrogen acceptor. Thus, 2-arachidonylglycerol, a putative endogenous cannabinoid ester, also may serve as a substrate for the transporter. Substrate recognition requires the presence of at least one cis double bond situated at the middle of the fatty acid carbon chain, indicating a preference for ligands whose hydrophobic tail can adopt a bent U-shaped conformation. On the other hand, uptake experiments with radioactively labeled substrates show that no fewer than four cis nonconjugated double bonds are required for optimal translocation across the cell membrane, suggesting that substrates are transported in a folded hairpin conformation. These results outline the general structural requisites for anandamide transport and may assist in the development of selective inhibitors with potential clinical applications.